Sultan of Sulu's Sabah claim : a case of 'long-lost' sovereignty? - Mohd Hazmi Mohd Rusli (2013)
The recent claim of sovereignty by the Sultan of Sulu over Sabah has sparked unease amongst both Sabahans and the Malaysian government. Is this claim valid under international law?